Pigments, total soluble phenols and lignin levels of coffee seedlings inoculated with Colletotrichum gloeosporioides - Maia, Fernanda Gonçalves Martins; Ogoshi, Claudio; Pierre, Rosana Oliveira; Vieira, Jucilayne Fernandes; Ribeiro junior, Pedro Martins; Abreu, Mario Sobral (Coffee Science - ISSN 1984-3909, 2012)
The objective of this work was to study the effects of different isolates of Colletotrichum gloeosporioides, as topigment level (chlorophyll a, b and total), total soluble phenols and soluble lignin in coffee seedlings obtained by artificially inoculatedtissue culture. The experiment was carried out in randomized block design in a 2 x 3 factorial scheme (2 genetic materials), 3 isolates(an isolate from mango fruits and another one from coffee plants), with 5 replicates and control (plants without inoculation). Theplants were inoculated with a suspension of 2 x 106 conidia.ml-1. The conidial suspension was sprayed on previously injured leaves.Leaves of inoculated plants were collected at 3 and 7 days after inoculation, except for leaves on the lower part of the plants.Afterwards, samples were prepared for the evaluation of chlorophyll, total soluble phenols and soluble lignin. The results showedthat the presence of the pathogen in healthy and diseased plants significantly reduced the amount of chlorophyll. At 7 days afterinoculation of healthy and diseased coffee plants higher total soluble phenol and soluble lignin levels were observed in response to theattack by Colletotrichum gloeosporioides.